Crimes of Solidarity in Mobility: Alternative Views on Migrant Smuggling. Issue 1 (March 2018) - Zhang, Sheldon X.; Sanchez, Gabriella E.; Achilli, Luigi
In this volume of The ANNALS, we present a collection of empirically based research projects on migrant smuggling, seeking to create a more nuanced understanding of the topic that supersedes perspectives that are often found in mainstream narratives of unscrupulous and ruthless criminal gangs preying on vulnerable and desperate migrants. The contributing authors rely on field data to reveal the complex and often symbiotic relationships between migrants and the people behind their journeys. Often misunderstood in juxtaposition to narratives of security and control, the lived experiences of migrants describe smuggling facilitators as relatives or close friends, acquaintances or distant operators—all members of a social network of varying relational proximity. Vulnerability in migration grows as the travel distance and transit points increase and the density of one's own community ties decreases. The procurement of smuggling services is always situated within the collective wisdom and lived experiences of the migrants and their communities, and the strategies to increase the odds of success and to reduce the hazards and uncertainty of traversing foreign terrains.